Predictors of older drivers' involvement in high-range speeding behavior. (17th February 2017) - Chevalier, Anna; Coxon, Kristy; Rogers, Kris; Chevalier, Aran John; Wall, John; Brown, Julie; Clarke, Elizabeth; Ivers, Rebecca; Keay, Lisa
ABSTRACT: Objective: Even small increases in vehicle speed raise crash risk and resulting injury severity. Older drivers are at increased risk of involvement in casualty crashes and injury compared to younger drivers. However, there is little objective evidence about older drivers' speeding. This study investigates the nature and predictors of high-range speeding among drivers aged 75–94 years. Methods: Speed per second was estimated using Global Positioning System devices installed in participants' vehicles. High-range speeding events were defined as traveling an average 10+km/h above the speed limit over 30 seconds. Descriptive analysis examined speeding events by participant characteristics and mileage driven. Regression analyses were used to examine the association between involvement in high-range speeding events and possible predictive factors. Results: Most (96%, 182/190) participants agreed to have their vehicle instrumented, and speeding events were accurately recorded for 97% (177/182) of participants. While 77% (136/177) of participants were involved in one or more high-range events, 42% (75/177) were involved in greater than five events during 12-months of data collection. Participants involved in high-range events drove approximately twice as many kilometres as those not involved. High-range events tended to be infrequent (median = 6 per 10, 000 km; IQR = 2–18). The rate of high-range speeding was associated with better cognitive function and attention to the driving environment. Conclusion: This suggests those older drivers with poorer cognition and visual attention may drive more cautiously, thereby reducing their high-range speeding behavior.